Factors Affecting Mobile Game Preference for Alpha Generation with MDA Games Analysis Framework - Rungsoongnern, Punyarat; Tirakoat, Suwich (Journal of Applied Informatics and Technology, 2025)
The purpose of this research is to 1) analyze mobile game design elements using an MDA framework, 2) study the factors affecting mobile game preference for the Alpha generation. Using the mobile game “Subway Surfers” as a case study, from a selection of free mobile games, and games content ratings not more than 13 years, this is a criterion for grading game content that is appropriate for the age of the Alpha generation, is a popular game available on both Android and iOS operating systems from the IGN website. The sample group consisted of 348 students from Assumption College Nakhon Ratchasima in Semester 2 of the 2023 academic year. The participants were selected using purposive sampling to ensure that they were able to use mobile phones fluently. The tools used to collect data were questionnaires on factors affecting the mobile games “Subway Surfers” among the Alpha generation. Statistics used in data analysis include sum and percentage. The results of the research found that 1) analysis of the mobile game “Subway Surfers” using the MDA framework reveals 17 factors that can be classified into 6 categories based on mechanics, 4 categories based on dynamics, and 7 categories based on aesthetics, 2) there are 11 factors that the Alpha generation likes the most, with more than 50 percent of respondents agreeing on each factor. These factors are: (1) friendly and easy-to-use control system, (2) the challenge of playing for as long as possible to get more points, (3) train the senses of using eyes, hands, and decision-making, (4) use the character controls to play the game from the original user experience, (5) the colors of the graphics in the game are bright and eye-catching, (6) the challenge of controlling the character through obstacles to reach the destination, (7) playing to relieve stress, (8) playing to kill time, (9) the character movements in the game are beautiful, (10) the sound in the game makes it feel fun, and (11) playable without an internet connection, respectively.